Soil erosion control and moisture conservation using contour ridge tillage in Bougouni and Koutiala, southern Mali - Traoré, K.; Zemadim, Birhanu (Scientific Research Publishing, Inc., 2019)
Soil erosion is among the critical environmental constraint for crop production in southern Mali. Contour ridge tillage (CRT), a water conservation technique had been locally applied since 1990. The objective of this study was to determine the effects of CRT compared with farmer conventional agriculture practice (NoCRT) on runoff, soil loss, nutrient loss, moisture conservation and cereals yields under rainfed conditions in two Southern Mali sites, in 2016 and 2017 in farmer fields. Measurements were performed on erosion plots composed of CRT and NoCRT plots from which water samples were collected to determine sedimentation levels, concentration and nutrients losses using pairwise comparison. Average runoff coefficient in NoCRT plots was 35.62% compared to 19.25% for the CRT plots explaining a runoff reduction of 46%. Mean soil losses of 12,095 t·ha−1 and 4970 t·ha−1 were respectively measured in NoCRT and CRT plots. Losses in calcium, magnesium and potassium nutrients in the NoCRT plots were 80%, 66%, 75% higher compared to CRT ones, respectively. Sorghum grain yield was at least two folds higher in CRT plots compared to the NoCRT plots. Maize average grain yield was 87% higher in CRT plots than in the NoCRT. For sustained soil productivity, CRT is advocated as a better soil and water management technique than the NoCRT one.